2005
DOI: 10.1293/tox.18.99
|View full text |Cite
|
Sign up to set email alerts
|

Harman and Norharman Suppressed but NaNO2 Enhanced the Development of Preneoplastic Liver Cell Foci in 2-Amino-3,8-Dimethylimidazo[4,5-f]Quinoxaline (MeIQx)-Treated Rats

Abstract: Abstract:The modifying potentials of two heterocyclic amines, harman and norharman, as well as sodium nitrite (NaNO 2 ), on 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx)-induced rat liver carcinogenesis were investigated using a medium-term liver bioassay system. Harman (500 ppm in diet), norharman (500 ppm in diet) or NaNO 2 (0.1% in drinking water) were given with or without MeIQx (300 ppm in diet) for 6 weeks after initiation with a single dose of dimethylnitrosamine (DEN). The appearance of MeIQx-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…21 On the other hand, enhancing effects of NaNO 2 on mammary carcinogenesis have not been shown when 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) was given to female rats as a carcinogen. 22 It has recently been shown that reactive nitrogen species produced by hemin effectively potentiated nitric oxidemediated nitrosation of IQ to 2-nitrosamino-3-methylimidazo [4,5-f]quinoline (N-nitroso-IQ), which can initiate colon cancer under inflammatory condition.…”
mentioning
confidence: 99%
“…21 On the other hand, enhancing effects of NaNO 2 on mammary carcinogenesis have not been shown when 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) was given to female rats as a carcinogen. 22 It has recently been shown that reactive nitrogen species produced by hemin effectively potentiated nitric oxidemediated nitrosation of IQ to 2-nitrosamino-3-methylimidazo [4,5-f]quinoline (N-nitroso-IQ), which can initiate colon cancer under inflammatory condition.…”
mentioning
confidence: 99%